2018
DOI: 10.1038/cmi.2017.147
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 induces immunosuppressive neutrophils via a type 2 innate lymphoid cell/IL-13/STAT6 axis and protects the liver against injury in LCMV infection-induced viral hepatitis

Abstract: Viral hepatitis is still a public health problem affecting several million people around the world. Neutrophils are polymorphonuclear cells that have a critical role in antibacterial infection. However, the role of neutrophils in viral infection is not fully understood. By using a mouse model of lymphocytic choriomeningitis virus infection-induced viral hepatitis, we observed increased neutrophil recruitment in the liver accompanied by enhanced CD8 T-cell responses. Liver neutrophils expressed high levels of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 65 publications
1
37
0
Order By: Relevance
“…18 Meanwhile, the higher neutrophil-to-lymphocyte ratio (NLR) at the 24th week after the onset of interferon treatment predicted the elimination of the replicative HCV-RNA strand in the liver during the antiviral treatment of patients with chronic hepatitis C. 19 In a viral hepatitis model induced by lymphocytic choriomeningitis virus infection, deletion of neutrophils increased the viral load, aggravated the T-cell response, and increased liver injury, while IL-33 treatment contributed to reducing liver inflammation by promoting the aggregation and immunosuppressive phenotype transformation of neutrophils within the liver. 20 In acute murine viral hepatitis, increased infiltration of neutrophils into liver tissue is also exacerbated by endogenous IL-33 deficiency. 21 These data indicated that IL-33 might be a target for reducing neutrophil infiltration in hepatitis, and IL-33 targeting therapy might benefit the outcome of viral hepatitis.…”
Section: The Role Of Neutrophils In Viral Hepatitismentioning
confidence: 99%
“…18 Meanwhile, the higher neutrophil-to-lymphocyte ratio (NLR) at the 24th week after the onset of interferon treatment predicted the elimination of the replicative HCV-RNA strand in the liver during the antiviral treatment of patients with chronic hepatitis C. 19 In a viral hepatitis model induced by lymphocytic choriomeningitis virus infection, deletion of neutrophils increased the viral load, aggravated the T-cell response, and increased liver injury, while IL-33 treatment contributed to reducing liver inflammation by promoting the aggregation and immunosuppressive phenotype transformation of neutrophils within the liver. 20 In acute murine viral hepatitis, increased infiltration of neutrophils into liver tissue is also exacerbated by endogenous IL-33 deficiency. 21 These data indicated that IL-33 might be a target for reducing neutrophil infiltration in hepatitis, and IL-33 targeting therapy might benefit the outcome of viral hepatitis.…”
Section: The Role Of Neutrophils In Viral Hepatitismentioning
confidence: 99%
“…8,16 However, studies using WT mice reveal that neutrophils are also recruited to sites of LCMV infection. [31][32][33][34] Based on this information, we next sought to investigate the contribution of T cells and neutrophils during primary HLH and the effects of ruxolitinib treatment upon them. Therefore, we quantified these lineages in the organs of LCMV-infected Prf1 2/2 mice that had been treated or not with ruxolitinib or aIFN-g.…”
Section: Ruxolitinib Reduces T-cell and Neutrophil Accumulation In Inmentioning
confidence: 99%
“…In a mouse model of choriomeningitis virus-induced hepatitis, IL-33 promoted neutrophil recruitment in the liver and dampened liver injury by limiting T-cell activation. Liver neutrophils displayed an immunosuppressive phenotype, characterized by high levels of arginase-1, iNOS and IL-10 ( 87 ). Thus, IL-33 may promote inflammatory or regulatory neutrophils, depending on the pathological condition.…”
Section: Immune Cell Targets Of Il-33 Affecting Tumor-immune Responsementioning
confidence: 99%